INTERNET OF THREATS. - Aguinaldo, Jennifer (MEED Business Review, 2017)
The article discusses how computer hacking was seen as niche form of criminal activity carried out by organised crime syndicates and cyber warfare demonstrated by Wannacry ransomware attack and the allegations of Russian interference in the U.S. presidential elections. Topics include cyber attacks experienced by Saudi Arabia in 2015, drive to increase efficiency through the digitalisation of processes and rebuilding information technology (IT) infrastructure to overhauling a brand.